MENINGKATKAN PRESTASI BELAJAR BAHASA INGGRIS MELALUI PEMBELAJARAN KOOPERATIF MODEL NUMBERED HEAD TOGETHER - ., Effendi (Makassar Journal of Social Sciences, 2015)
Abstract; This research aims to: (a) To reveal the influence of cooperative learning model of Numbered Head Together the results of learning English. (B) Want to know how far the understanding and mastery of subjects in English after the implementation of cooperative learning model of Numbered Head Together. This study used action research (action research) a total of three rounds. Each round consists of four phases: design, activities and observation, reflection, and refisi. This research target is Class VIII students. Data obtained in the form of a formative test results, observation sheet teaching and learning activities. From the analyst found that student achievement has increased from cycle I to cycle III, namely, the first cycle (60.71%), Cycle II (75.00%), the third cycle (89.29%). Results of this research is the model of cooperative Numbered Head Together can be a positive effect on student learning motivation VIII, and this model can be used as an alternative English